A Sociological Review of The Damaging Criminal Act - Gustika Sandra (Journal of Indonesian Scholars for Social Research, 2021)
This research aims to identify the role of vandalism in crime and the variables that affect it. This study used a qualitative approach, using a descriptive-analytic research design, to explore and comprehend a phenomenon explored further in future research. Purposive sampling was used to identify informants for this study in Bone Regency. Techniques for gathering data include observation, interviews, and documentation. Data analysis involves reducing data, displaying it, and making conclusions. According to the study's findings, illegal actions using sharp weapons do occur on occasion. Several variables affect this, including economics, education, the fight for power, and the environment. It may accomplish this via counseling in high-crime regions and instruction beginning in elementary school. To address the core of the issue directly and teach knowledge from the start to preserve societal harmony. If it is not avoided, the methods of destruction used in society will result in a loss of tranquility.